Collaborative Multi-racial Post-election Survey (CMPS), United States, 2016 - Frasure, Lorrie ([Verlag nicht ermittelbar], 2021)
In spring 2016, scholars were invited to collaborate on the 2016 Collaborative Multi-Racial Post-election Survey (CMPS). The goal of the project was to create the first cooperative, 100% user content driven, multi-racial, multiethnic, multi-lingual, post-election online survey in race, ethnicity and politics (REP) in the United States. The survey's main focus is on attitudes about the 2016 election and candidates, debates over immigration, policing, and racial equality, and experiences with racial discrimination across many facets of American life. Questions were user-generated from a team of 86 social scientists across 55 different universities who placed questions on the survey. Users could submit questions for just one single racial group, or common questions across all four racial groups, depending on their interest. In cases where two different users submitted very similar questions the PIs worked to create a single common question. Overall, the survey contains 394 questions. The restricted-use dataset contains geographical information which has been masked in the public-use dataset along with adjustments to date information. Please refer to the Collection Notes in the SCOPE OF PROJECT section for more information.